ANALISIS KECOCOKAN BAHAN CORDURA UNTUK TAS HEWAN PELIHARAAN - Anjerina Hartanto Widjaya; Claudia Glory Marchatmyna; Wilson Patrick Tirtamidjaja; Meirista Wulandari (Jurnal Mitra Teknik Industri, 2026)
The growing number of pet owners in urban areas has led to an increasing demand for pet carriers that offer safety, comfort, and durability. Cordura is one of the materials often considered because of its well-known strength, tear resistance, abrasion resistance, and easy maintenance. This paper aims to evaluate how suitable Cordura is as the primary material for pet carriers by examining several aspects, including durability, water resistance, texture comfort, lightness, and ease of cleaning. A quantitative approach was used by distributing questionnaires to 50 pet owners. The collected data were analyzed using the Kolmogorov-Smirnov test to assess normality and the Chi-Square test to determine the relationship between Cordura’s characteristics and its perceived suitability for pet carriers. The results indicate that the data follow a normal distribution (sig. 0.184) and that there is a significant relationship between Cordura’s attributes and its suitability for use in pet carriers (sig. 0.000). These findings show that Cordura offers the essential qualities needed for pet carriers, providing a combination of safety, comfort, and long-lasting durability that aligns with the expectations of pet owners.